Specialized Transducing Phages Derived from Salmonella Phage P22 - Hoppe, Ingrid (1974)
Salmonella phage P22 has been used in the construction of three sorts of specialized transducing phage: P22 proAB, P22 proABlac and P22 argF. The bacterial genes carried are derived from E. coli K12. Since E. coli and Salmonella chromosomes recombine very poorly, E. coli genes cannot be transduced into Salmonella recipients by P22's generalized transduction mechanism. Therefore, stable inheritance of E. coli material provides a means of detecting specialized transduction. Formation of these phages was possible because the P22 prophage recognizes an attachment site in the E. coli F' prolac episome. Salmonella strains carrying the F' prolac episome can be lysogenized by P22 so as to leave the prophage inserted into the E. coli material of the F' factor. Improper prophage excision can then lead to formation of P22 specialized phages carrying E. coli genetic material.